Unilateral Giant Hydronephrosis Secondary to Ureteropelvic Junction Obstruction in a Middle-Aged Woman. (4th September 2021) - Dino, Masresha S.; Hassen, Seid M.; Tufa, Tesfaye H.
Abstract : Background . Giant hydronephrosis is a rare urologic problem defined as a collection of more than one liter of urine in the collecting system. The radiologic appearance may mimic benign cystic disease of the kidney. We report a case of giant hydronephrosis in a 32-year-old female who presented with progressive abdominal swelling of two-year duration, caused by ureteropelvic junction obstruction with more than nine liters of urine in the collecting system. Conclusion . Giant hydronephrosis is a rare differential diagnosis for cystic intra-abdominal mass in adults with progressively increasing abdominal swelling. CT and MRI are important in confirming the diagnosis by localizing the origin of the swelling. Management depends on the underlying cause and appearance of the diseased kidney.